Simplification of thermal calibration for MEMS accelerometers - Martínez Lahoz, Javier; Asiain Ansorena, David; Beltrán Blazquez, José Ramón (Jornada de Jóvenes Investigadores del I3A, 2021)
The thermal drifts of MEMS inertial sensors limit their use, due to the cost of their calibration. Simplifying thermal calibration and compensation methods can reduce the cost and equipment required. In this work, a light compensation algorithm with its corresponding rapid calibration technique is proposed.